Corrigendum: Coping Behaviors and Psychological Disturbances in Youth Affected by the COVID-19 Health Crisis (Frontiers in Psychology, (2021), 12, (565657), 10.3389/fpsyg.2021.565657) - Orgilés, Mireia (2021)
In the original article, there was an error. All results that were statistically significant were informed, rather than only those that were found to be significant after applying the Bonferroni adjustment. A correction has been made to Results, Coping Strategies, Paragraph 1. The corrected paragraph is shown below. Table 2 shows the proportion of children using coping strategies during the home confinement due to COVID-19. Themost frequently used coping strategy was acceptance, withmore than half of the parents reporting that their children use it (58.9%). Other commonly used coping strategies (at least 30% of the children) were collaborating with social activities such as drawings on windows or collective applauses (35.9%), ignoring the problem and acting as if nothing was happening (35.5%), highlighting the advantages of being at home (35.1%), seeking comfort from others (31%), and not showing concern about what was happening (30.1%). According to age, the most used coping strategies (more than 30% of parents reported that their children used them) were similar among preschool children, school-age children, and adolescents, although their order could differ for each group. In preschool children (3–5 years), the most used coping strategies were: accepts what’s going on (45.5%) (Task-oriented); acts as if nothing is happening (44.4%) (Avoidance-oriented); doesn’t seem to care what is happening (40%) (Avoidance-oriented); and seeks affection from others (36.9%) (Emotional-oriented). In the school-age children (6–12 years), themost used coping strategies were: accepts what’s going on (60.6%) (Task-oriented); highlights the advantages of being at home (41.3%) (Task-oriented); seeks affection from others (33.8%) (Emotion-oriented); and acts as if nothing is happening (32.3%) (Avoidance-oriented). In the adolescent group (13–18 years), the most used strategies were: accepts what’s going on (69.9%) (Task-oriented); highlights the advantages of being at home (37.9%) (Task-oriented); and acts as if nothing is happening (32.2%) (Avoidance-oriented). When comparing the three countries, and after applying for Bonferroni correction, Spanish children were more likely to collaborate in social activities than children from the other countries. Compared to the Italian children, those from Portugal were also more likely to collaborate in social activities. Spanish children were more likely to seek affection in others, compared to the rest of children. Italian children weremore likely to act as if they were not worried about what was happening, compared to the rest. Compared to the Portuguese children, those from Spain were also more likely to seem worried about what is happening. Additionally, a correction has been made to Discussion, Paragraph 2. Results show that the most frequently used coping strategy was task-oriented (accepting what was happening), with 59% of parents reporting its use by their children. Also, at least 30% of the children collaborated in social activities, acted as if nothing was happening, highlighted the advantages of being at home, sought comfort from others, or did not seem worried about what was happening. Differences by countries show interesting results. Collaborating in social activities and seeking comfort from others were more likely in Spanish children than in children from the other countries. Compared to Portuguese and Spanish children, Italian children did not seem worried about what was happening. Although it is unclear, the different rules of confinement imposed by each country could explain these differences. Portugal followed voluntary confinement, so maybe children’s routines did not change as much as in the other countries; the few cases of infections and deaths compared to Spain and Italy might have contributed to their not perceiving the situation as dangerous. Children from Spain used adaptive strategies to cope with the situation, such as collaborating in social activities, but they were also more likely to seek comfort from their parents. Spain had the most restrictive confinement rules, not allowing children to go outside until April 26th. Although more data are necessary to explain this finding, the interruption of all social contact and staying at home with the parents for such a long time could have encouraged Spanish children to seek more comfort than Portuguese and Italian children, who followed a less restrictive confinement. Also, Spanish children collaborated more in social activities, such as collective applauses from the balconies or windows, probably showing their need for social contact with others, which was limited indoors. Finally, Italian children seem less concerned about the situation than children from the other countries. Unlike Italy, Portugal used voluntary confinement, with habits and routines depending on each family’s decision, so the children may have perceived inconsistent situations outdoors that might have worried them. Italian children were allowed to go outside before Spanish children, so Spanish children may have been more worried than Italian children because they had to follow the prohibition of going outside. Although further research is needed, allowing Italian children to go outside whilemaintaining consistent rules for all the children (a walk with one adult near their house) may have reduced their concerns. There were also errors in Tables 2 and 5 as published. The corrected Tables 2 and 5 are shown below. The authors apologize for these errors and state that they do not change the scientific conclusions of the article in any way. The original article has been updated. (Table presented.).